Containment of Ebola and Polio in Low-Resource Settings Using Principles and Practices of Emergency Operations Centers in Public Health. Issue 1 (January 2017) - Shuaib, Faisal M.; Musa, Philip F.; Muhammad, Ado; Musa, Emmanuel; Nyanti, Sara; Mkanda, Pascal; Mahoney, Frank; Corkum, Melissa; Durojaiye, Modupeoluwa; Nganda, Gatei wa; Sani, Samuel Usman; Dieng, Boubacar; et al.
Abstract : Emergency Operations Centers (EOCs) have been credited with driving the recent successes achieved in the Nigeria polio eradication program. EOC concept was also applied to the Ebola virus disease outbreak and is applicable to a range of other public health emergencies. This article outlines the structure and functionality of a typical EOC in addressing public health emergencies in low-resource settings. It ascribes the successful polio and Ebola responses in Nigeria to several factors including political commitment, population willingness to engage, accountability, and operational and strategic changes made by the effective use of an EOC and Incident Management System. In countries such as Nigeria where the central or federal government does not directly hold states accountable, the EOC provides a means to improve performance and use data to hold health workers accountable by using innovative technologies such as geographic position systems, dashboards, and scorecards.